Impact of prenatal stress on the dyadic behavior of mothers and their 6-month-old infants during a play situation: role of different dimensions of stress - Wolf, Isabell Ann-Cathrin; Deuschle, Michael; Laucht, Manfred (Journal of neural transmission, 2017)
Prenatal stress (PS) is an established risk factor in the etiology of mental disorders. Although mother-child interaction is the infant’s first important training in dealing with stress, little is yet known about the impact of PS on mother-infant dyadic behavior. The current study aimed to elucidate the prospective influence of psychological and physiological stresses during pregnancy on mother-infant dyadic behavior. Mother-infant interactions were videotaped at 6-month postpartum and coded into three dyadic patterns: (1) both positive; (2) infant protesting-mother positive; and (3) infant protesting-mother negative, using the infant and caregiver engagement phases. Exposure to PS was assessed during pregnancy using psychological (i.e., psychopathological, perceived, and psychosocial PS; n = 164) and physiological stress measures (i.e., maternal cortisol; n = 134). Group comparisons showed that psychosocial PS was predictive of mother-infant behavior at 6-month postpartum, indicating that dyads of prenatally high-stressed mothers exhibited significantly more positive interaction patterns (i.e., infant positive-mother positive) as compared to the prenatally low-stressed group. Physiological PS was unrelated to mother-infant behavior. These results suggest that mild psychosocial PS may be advantageous for positive mother-infant dyadic behavior, which is in accordance with the stress-inoculation model that assumes a beneficial effect of PS.
Gesehen am 29.08.2018